2008
DOI: 10.1111/j.1471-4159.2008.05721.x
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric measurements of catecholamine release from single vesicles in MN9D cells

Abstract: MN9D cells have been used as a successful model to investigate dopamine pharmacology and to test the specific effects of drugs for the treatment of Parkinson’s disease. However, quantitative measurements of quantal release from these cells have not been carried out. In this work, we used amperometry to investigate catecholamine release from MN9D cells. Amperometric events were observed in both undifferentiated and differentiated (butyric acid‐treated) cells. An increase in quantal size and half‐width was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…First we established that our model, MN9Dsyn cells, express the rate-limiting enzyme for catecholamine synthesis, tyrosine hydroxylase, dopamine transporter and vesicular monoamine transporter 2, which is consistent with previous studies that demonstrated the ability of the MN9D parental cells to produce, transport and store dopamine (Choi et al, 1991a; Chen et al, 2005; Zhou et al, 2006; Dong et al, 2008). We also demonstrated an enhancement of α-synuclein-induced toxicity in the presence of both dopamine and paraquat.…”
Section: Discussionsupporting
confidence: 89%
“…First we established that our model, MN9Dsyn cells, express the rate-limiting enzyme for catecholamine synthesis, tyrosine hydroxylase, dopamine transporter and vesicular monoamine transporter 2, which is consistent with previous studies that demonstrated the ability of the MN9D parental cells to produce, transport and store dopamine (Choi et al, 1991a; Chen et al, 2005; Zhou et al, 2006; Dong et al, 2008). We also demonstrated an enhancement of α-synuclein-induced toxicity in the presence of both dopamine and paraquat.…”
Section: Discussionsupporting
confidence: 89%
“…With current sampling rates in the kHz range, this technique can resolve signals on time scales below milliseconds. This technique has been successfully used for studies of catecholamine concentrations in the brain and in brain slices [125, 126], exocytosis of the small synaptic vesicles [127], neuroblastoma, and other cells [128, 129]; it has the best temporal resolution because of sampling rates down to 1 ms. However, the disadvantage of DC amperometry is that it is essentially nonselective, because all electroactive compounds that oxidize (or reduce) at the applied potential will produce a faradaic response at the electrode.…”
Section: Electrochemical Techniques For Detection Of Dopamine With Immentioning
confidence: 99%
“…26 For instance, several reports using amperometry have found significant quantitative and kinetic information, and have proposed various cellular or molecular mechanisms controlling exocytosis. 711 …”
Section: Introductionmentioning
confidence: 99%